Nationwide epidemiological survey of familial myelodysplastic syndromes/acute myeloid leukemia in Japan: a multicenter retrospective study. Issue 7 (6th June 2020) - Takaoka, Kensuke; Koya, Junji; Yoshimi, Akihide; Toya, Takashi; Kobayashi, Takashi; Nannya, Yasuhito; Nakazaki, Kumi; Arai, Shunya; Ueno, Hironori; Usuki, Kensuke; Yamashita, Takeshi; Imanishi, Daisuke; et al.
Abstract: Although several pedigrees of familial myelodysplastic syndromes/acute myeloid leukemia (fMDS/AML) have been reported, the epidemiology and clinical features has been poorly understood. To explore the epidemiology of this entity, we performed a retrospective nationwide epidemiological survey in Japan using questionnaire sheets. The questionnaire was sent to 561 institutions or hospitals certified by Japanese Society of Hematology, unearthing the existence of 41 pedigrees of fMDS/AML. Among them, we obtained the clinical information of 31 patients in 20 pedigrees. The median age of the initial diagnosis was 51 years (range 9–88 years) and the WHO classification 2008 ranged from refractory anemia (RA) to AML. Focusing on the familial MDS patients, refractory anemia with excess blasts (RAEB)-2 was the largest group (27.3%). The median overall survival (OS) of fMDS and fAML in this study were 71.6 and 12.4 months, and the five-year OS were 61.3 and 50%, respectively.